Thrombotic microangiopathy following heart transplant in pediatric Danon disease. (18th February 2020) - Hummel, Kevin; Glotzbach, Kristi; Menon, Shaji; Griffiths, Eric; Lal, Ashwin K.
Abstract: This case describes an uncommon acute complication of diffuse thrombotic angiopathy and associated aHUS/TTP in an 11‐year‐old girl with Danon disease who underwent orthotopic heart transplant. Shortly after transplant, despite an uncomplicated operative course, the patient developed severe kidney injury and progressive altered mental status, culminating in cerebral edema, brain herniation, and death. She had received a single dose of tacrolimus (FK506) and a single dose of antithymocyte globulin. Sources of progressive somnolence, including oversedation from impaired renal clearance of opiates, and severe myopathy as has been previously described in Danon disease, were ruled out, and the patient continued to decline. Initial brain CT scan early after transplant showed no signs of cerebral edema, but repeat CT indicated severe cerebral edema. Based on autopsy, diffuse thrombotic angiopathy, with signs of hemolytic anemia with schistocytes, was likely responsible for her deterioration in the broader condition of aHUS/TTP.